Jacques Rancière and Care Ethics: Four Lessons in (Feminist) Emancipation - Sophie Bourgault (Philosophies, 2022)
This paper proposes a conversation between Jacques Rancière and feminist care ethicists. It argues that there are important resonances between these two bodies of scholarship, thanks to their similar indictments of Western hierarchies and binaries, their shared invitation to “blur boundaries” and embrace a politics of “impropriety”, and their views on the significance of storytelling/narratives and of the ordinary. Drawing largely on Disagreement, Proletarian Nights, and The Ignorant Schoolmaster: Five Lessons in Intellectual Emancipation, I also indicate that Rancière’s work offers crucial and timely insights for care ethicists on the importance of attending to desire and hope in research, the inevitability of conflict in social transformation, and the need to think together the transformation of care work/practices and of dominant social norms.